2022
DOI: 10.31849/elsya.v4i2.8732
|View full text |Cite
|
Sign up to set email alerts
|

Hospitality School Students’ Perception on the Use of Wordwall to Enrich Students’ Work-Ready Vocabulary Mastery

Abstract: This study addressed the gap of research on the innovative learning medium Wordwall for working adult learners by investigating the perceptions of students of Apollonia Hotel School in Denpasar, Indonesia, regarding how well Wordwall helps in increasing their English vocabulary during online learning. The method used by the researcher was qualitative. Data were collected from 10 respondents who had been selected with qualifications of activeness while studying, and always participated during the process. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Even yet, the students occasionally complained about the internet network, which caused the Wordwall.net application not to work correctly. However, Wordwall.net requires a strong internet connection, so it may be used to answer quizzes without a hitch (Arsini et al, 2022;Elaish et al, 2019). Thus, if there were no problems with the internet connection and the application could run smoothly, it might allow for more effective vocabulary learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even yet, the students occasionally complained about the internet network, which caused the Wordwall.net application not to work correctly. However, Wordwall.net requires a strong internet connection, so it may be used to answer quizzes without a hitch (Arsini et al, 2022;Elaish et al, 2019). Thus, if there were no problems with the internet connection and the application could run smoothly, it might allow for more effective vocabulary learning.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, teachers must create effective vocabulary teaching so that the students can excel in their academic life and overall competencies in English (Babaei & Ahour, 2016;Ngaiza & Sivashanmugam, 2020). Following the trend of modern educational technology, many scholars advise adopting digital games to aid students in expanding their vocabulary knowledge (Arsini et al, 2022;Ibrahim et al, 2022). Implementing digital games in educational contexts and aims for learning is not a new phenomenon; this teaching strategy is more commonly known as Digital Game-Based Learning (DGBL).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Jannah and Syafryadin (2022) reported favorable student responses to using Wordwall.net as a vocabulary learning tool, citing its engaging and motivational qualities. Research by Arsini et al (2022) on hospitality students indicated that Wordwall's vocabulary games significantly boosted learning enthusiasm, despite some limitations in providing detailed explanations. Susanto and Yosephine (2019) discussed teachers' perceptions of incorporating word games into writing instruction, noting the need for creativity and emphasis on learning objectives over game mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Firdiansyah and Pamungkas (2021) investigated how students felt about the usage of Kahoot as a learning assessment tool in the course on monetary economic theory. The perceptions of students at hotel school toward the usage of word-wall to enhance student workready vocabulary mastery were the subject of research by Arsini et al (2022). According to the data analysis, students are quite enthusiastic about using the word-wall application to learn new words.…”
Section: Introductionmentioning
confidence: 99%